Exploring the Use of Social Media for Adult Health Education: A Case Study of Aproko Doctor (Unilorin Journal of Lifelong Education, 2025)
Adults engage with social media platforms like YouTube, X, Facebook, and Instagram for reasons such as connecting with people, marketing, professional networking, and seeking entertainment. While studies have examined social media engagement, limited focus has been given to the learning content and teaching strategies of Aproko Doctor, a Nigerian health content creator. This study explored the motivations behind subscribers following Aproko Doctor's social media channels, their learning outcomes, and the teaching methods used in his educational content delivery. A mixed-method research design was adopted, utilizing questionnaires and interview guides for data collection. Quantitative data were analysed using frequency counts and percentages, while thematic analysis was applied to qualitative data. Two hundred and seventy Aproko Doctor's subscribers were selected for the study. Findings showed that subscribers followed him for health updates, education, and his simplistic approach to content delivery. They reported learning to debunk health-related myths and adopting healthier habits. The demonstration method accompanied with humour and comedy is the most prominent teaching method and strategy adopted by Aproko Doctor. The study concludes that adult learners are motivated to follow health content creators for the learning outcomes and captivating teaching methods, highlighting social media's potential to enhance adult health education.